DEVELOPING STUDENTS SPEAKING THROUGH COMMUNICATIVE LANGUAGE TEACHING APPROACH AT ENGLISH LESSON - G. A. Salomova; O. Yusupov (The Conference Hub, 2025)
This article explores various methodologies and strategies aimed at increasing communicative talking in English lessons, emphasizing student-centered learning and the role of interaction. Effective communication is a fundamental component of language acquisition. In English lessons, fostering communicative talking is essential for developing students' speaking skills. By analyzing existing literature on communicative language teaching (CLT) and task-based learning (TBL), this study highlights the effectiveness of group activities, real-world tasks, and role-play in enhancing speaking skills. Furthermore, it discusses the challenges and limitations of implementing these methods in diverse classroom settings and offers recommendations for maximizing student participation in communicative exercises.
Keywords: CLT, TBL, speaking skill, communication, English, role-play, student-centered